Pengaruh Variety Seeking Terhadap Brand Switching dengan Product Attributes Sebagai Variabel Moderasi dalam Perspektif Manajemen Bisnis Syariah - Ema Seftiana; Dimas Pratomo; Zathu Restie Utami (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
Variety Seeking is a person's action in looking for something else because of a sense of saturation in the use of a product so that looking for new things and doing Brand Switching is the solution, in that process seeing the advantages and disadvantages of product attributes becomes a determining factor especially in Gen-Z who really sees something that has advantages is definitely interested in trying. The population in this study is Gen-Z who are in Bandar Lampung with the criteria that the researchers have determined. The sample size was 100 respondents. This research method is quantitative with online questionnaire data collection techniques through google form with the analysis method using a structural equation model approach with the SmartPLS 4 application. The results showed that Variety Seeking has a positive and significant effect on Brand Switching, and the next results show that Product Attributes moderate strengthen and significant the relationship between Variety Seeking and Brand Switching, superior attributes are the reason people try other variations and switch brands.